NETWORK PHARMACOLOGY AND MOLECULAR DOCKING TECHNIQUES TO EXPLORE THE PHARMACOLOGICAL MECHANISM OF CATECHINS AND THEIR DERIVATIVES AGAINST METABOLIC SYNDROME - RODRIGUES, OLIVIA (Innovare Journal of Medical Sciences, 2023)
Objective: Metabolic syndrome (MetS) is one of the most prevalent disorders in both industrialized and developing nations that it is characterized by a set of risk variables that encompass abdominal obesity, dyslipidemia, hypertension, and insulin resistance MetS constitutes a collective set of cardiometabolic attributes that raise the risk of type 2 diabetes mellitus and cardiovascular diseases. Catechins possess anti-inflammatory and antioxidant effects which may provide defense against many chronic diseases. The present study attempts to associate the pharmacological benefits of catechins and their derivates against MetS using in silico approaches. Methods: Identification of the ligands and target proteins was done using drugbank and protein-protein interaction network stitch, respectively. The ligands and proteins were docked using pyrx and the docked complexes were visualized on BIOVIA to identify the potential ligand. ADMET analysis was done for the same ligands to study their pharmacological properties. Results: The proteins glutathione peroxidase 1 and tumor protein P53 were identified as target proteins expressed in MetS which also showed effective docking results with the ligands hesperidin and gamma-tocopherol, respectively. The study’s findings concurred with those of earlier studies indicating that the derivatives of catechins such as hesperidin and gamma-tocopherol had potential benefits in the prognosis of MetS. Conclusion: The investigation findings concluded that the ligands hesperidin and gamma-tocopherol may be therapeutic against MetS prevention and management.